Fecal microbial signatures of healthy Han individuals from three bio-geographical zones in Guangdong - Huang, Litao; Deng, Liting; Liu, Changhui; Huang, Enping; Han, Xiaolong; Xiao, Cheng; Liang, Xiaomin; Sun, Huilin; Liu, Chao; Chen, Ling (Frontiers in Microbiology, 2022)
Important forensic evidence traced from crime scene, such as fecal materials, can help in forensic investigation of criminal cases. Intestines are the largest microbial pool in human body whose microbial community is considered to be the human “second fingerprint”. The present study explored potential for community characteristics of gut microbes in forensic medicine. Fecal microbiota profiles of healthy individuals from three representative Han populations (Guangzhou, Shantou and Meizhou) in Guangdong Province, China was evaluated using High-throughput sequencing of V3-V4 hypervariable regions of 16SrRNA gene. Results of the present study showed that at the genus level, Shantou, Guangzhou, and Meizhou behaved as Enterotpye1, Enterotype2, and Enterotype3, which were mainly composed of Bacteroides, Prevotella, and Blautia, respectively. Based on OTU abundance at the genus level, the random forest prediction model found that there might be potential of distinguishing individuals of Guangzhou, Meizhou and Shantou according to their fecal microbial community. Moreover, the findings of the microbial community of fecal samples in the present study was significantly different from that of saliva samples reported in our previous study and thus it is evident that the saliva and feces can be distinguished. In conclusion, this study reported the fecal microbial signature of three Han populations, which may provide basic data for the potential application in forensic practice, containing body fluid identification, and geographical inference.